Flipped Learning with Nearpod Media: Enhancing Digital Learning Outcomes in Primary Mathematics - Sari, Riska Monicca; Rusnilawati, Rusnilawati; Ali, Siti Rahaimah (Universitas Muhammadiyah Surakarta, 2023)
This investigation examines the efficacy of the Flipped Learning Model, supplemented with Nearpod media, on the academic outcomes of fifth-grade students in the subject of fractions. Utilising a quantitative methodology within a quasi-experimental research design, the Flipped Learning Model was deployed over three sessions. Nearpod media was employed to stimulate student engagement and enhance academic outcomes. A comparative study was conducted between students who were subjected to the Flipped Learning Model with Nearpod media (N=12) and a control group (N=12) that utilised the Direct Learning Model with image media. The analysis revealed a significant discrepancy in academic outcomes between the two groups (0.023, p < 0.05). Throughout the investigation, students who were exposed to the Flipped Learning Model with Nearpod media showed an improvement in academic outcomes (Mchange= 0.000, p < 0.05), indicating a significant influence on students' mathematical learning. The integration of the Flipped Learning Model with Nearpod media was found to be notably effective in improving students' academic outcomes (0.67, 0.03<g<0.7). This confirms that the implementation of the Flipped Learning Model with Nearpod media has a significant impact on enhancing classroom academic outcomes.